2007
DOI: 10.1089/aid.2006.0203
|View full text |Cite
|
Sign up to set email alerts
|

The Close Relationship between South African and Latin American HTLV Type 1 Strains Corroborated in a Molecular Epidemiological Study of the HTLV Type 1 Isolates from a Blood Donor Cohort

Abstract: It has been difficult to explain why all HTLV-1 sequences in Salvador, a city in the northeast of Brazil, belong to the Transcontinental (A) subgroup of the Cosmopolitan (a) subtype, since according to historical data the vast majority of slaves brought to Brazil (through Salvador) came from west Africa, where only the western African subgroup (C) has been found. To shed more light on this subject we conducted a phylogenetic analysis of 23 isolates from blood donors of Salvador. DNA was extracted and submitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…The grouping of the Brazilian HTLV-1 sequences into different subclusters support the hypothesis that there were multiple introductions of the transcontinental subtype in Brazil. These findings further support several studies conducted in some Brazilian and other Latin American populations that suggested the introduction of HTLV-1 on multiple occasions and that demonstrate an association between the Latin American cluster with sequences of African origin [37], [43], [44], [45], [46]. The results of detecting HTLV-1 aA and aB among patients of Japanese descent is consistent with previous data described among Japanese immigrants in Sao Paulo, where the detection of both sub-subtypes has been reported [17], [35], [47], [48].…”
Section: Discussionsupporting
confidence: 89%
“…The grouping of the Brazilian HTLV-1 sequences into different subclusters support the hypothesis that there were multiple introductions of the transcontinental subtype in Brazil. These findings further support several studies conducted in some Brazilian and other Latin American populations that suggested the introduction of HTLV-1 on multiple occasions and that demonstrate an association between the Latin American cluster with sequences of African origin [37], [43], [44], [45], [46]. The results of detecting HTLV-1 aA and aB among patients of Japanese descent is consistent with previous data described among Japanese immigrants in Sao Paulo, where the detection of both sub-subtypes has been reported [17], [35], [47], [48].…”
Section: Discussionsupporting
confidence: 89%
“…Different HTLV-1 genotypes exist, some of which are geographically restricted: Genotypes b and d to g are restricted to central Africa, while genotype c is endemic in Australo-Melanesia. In contrast, the cosmopolitan genotype a is widely distributed, supposedly dispersed during the past centuries through migration of infected populations, as for instance during the Atlantic slave trade (6,(9)(10)(11). Within this large cosmopolitan a subtype, several molecular clades have been described (e.g., Japanese and West African).…”
mentioning
confidence: 99%
“…Mozambique is located on the southeast region of the continent, and the presence of HTLV-1 has also been reported in countries that share borders with Mozambique [40]. The characterization of HTLV-1 Transcontinental subgroup as the prevalent subgroup driving the HTLV epidemics in Mozambique, and South Africa [38] shows that there are, at least, two major endemic lineages of Cosmopolitan HTLV-1 in Africa. One, dominating the Northwestern part of the continent, driven by HTLV-1aD trans-Saharan lineage, as proposed by Zehender [14] and a second lineage in Southern countries, determined by Transcontinental HTLV-1 subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…The sub-Saharan Africa is considered to be endemic for HTLV-1 infection, with overall seroprevalence rates in Western and Central African countries being similar to the ones observed in Eastern and Southern African countries [17], [18], [36][38]. However, there is lack of data concerning the HTLV molecular epidemiology in Eastern African countries, contrasting with studies in Western countries and South Africa [14], [39].…”
Section: Discussionmentioning
confidence: 99%